PENGEMBANGAN MODEL LATIHAN KOMBINASI DRIBBLING, PASSING DAN SHOOTING PESERTA EKSTRAKURIKULER BOLABASKET DI SMP NEGERI 2 KOTA MALANG - Anugerah Budhi Darmawan; Oni Bagus Januarto; Usman Wahyudi (Fakultas Ilmu Keolahragaan UM)
Abstract: The purpose of this research and development is to develop a model of combination drills dribbling, passing and shooting for extracurricular participants basketball Junior High School 2 Malang. This study uses three experts, namely the expert coaching with the results of 85.65%, a basketball with the results of 75.20% and a basketball expert with the results of 76.60%. While testing a small group obtained 83.80% and 85.25% test large groups. So it can be concluded that the research and development of models of combination drills dribbling, passing and this shooting is feasible and can be used for basketball extracurricular participants in Junior High School 2 Malang.Keyword: extracurricular, dribbling, passing, shooting